EVALUATION OF TENDON HEALING AFTER ARTHROSCOPIC REPAIR OF ISOLATED SUPRASPINATUS TEARS - Guilherme José Costa Ferreira; Marlos Augusto Bitencourt Costa; Rubens Carneiro dos Santos Neto; Marcos Rassi Fernandes (Acta Ortopédica Brasileira)
ABSTRACT Objective: To evaluate the healing of supraspinatus tendon lesions after arthroscopic repair, with analysis of intra- and inter-observer agreement by two experienced evaluators for the same lesions. Materials and Methods: A study was conducted with patients evaluated in the postoperative period of arthroscopic surgery to repair isolated supraspinatus tendon ruptures, with a minimum follow-up of one year. Tendon healing was evaluated using magnetic resonance imaging by two independent evaluators at two time points, with a seven-day interval between them. Categorical data were presented in absolute and relative frequencies, and mixed linear regression models were used to analyze intra- and inter-observer agreement, with a probability of rejecting the null hypothesis of 5%. Results: Twenty-three patients (26 shoulders) were evaluated, with a mean age of 61.5 years. At both evaluation times, most patients presented a healing grade between I and III in the Sugaya classification for both observers. The interobserver agreement was good, and the intraobserver agreement was excellent. Conclusion: The mean tendon healing rate for arthroscopic repair of isolated supraspinatus ruptures was 81.7%. Intra-observer agreement ratings were considered excellent, while inter-observer agreement was good, demonstrating reliability in the evaluations performed. Level of Evidence II; Cross-sectional study.